Penanganan psikologis terhadap korban kekerasan seksual - Saputra, Micho Triana (Maliki Interdisciplinary Journal, 2025)
Trauma resulting from sexual violence can have a significant impact on the mental health of sexual violence survivors. This research explores the effectiveness of psychological therapy as the main approach to dealing with the trauma of sexual violence. Through specific research designs, for example: case studies, experimental, we investigate the impact of psychological therapy on survivors' recovery with a focus on changes in behavior, emotional responses, and changes in psychological well-being. The findings of this study provide in-depth insight into the role of psychological therapy in supporting survivors of sexual violence in overcoming their trauma.